A comprehensive ecological compensation indicator based on pollution damage – protection bidirectional model for river basin. (July 2021) - Guan, Xinjian; Liu, Meng; Meng, Yu
Highlights: Subject-object compensation relationship was defined from damage and protection. The IPDC and IPPC were proposed to obtain the comprehensive compensation indicator. A bidirectional model for ecological compensation was constructed. Watershed pollution damage compensation is still the main compensation mode. The bidirectional ecological compensation mode needs to be taken seriously. Abstract: Watershed ecological compensation has important practical significance for water environment management and ecological protection. This study constructed a Pollution Damage – Protection Bidirectional model for eco-compensation (Bidirectional Model), which consisted of the pollution damage compensation module (PDC Module) and the pollution protection compensation module (PPC Module). The pollution damage compensation index (IPDC ) and the pollution protection compensation index (IPPC ) were calculated separately to obtain the comprehensive compensation value indicator (CI). The Xiaohong River Basin in Zhumadian, China was selected as the case study area, the bidirectional eco-compensation values (including damage compensation value (DCV) and protection compensation value (PCV)) in the four counties in the river basin from 2012 to 2015 were calculated. The results showed that the DCV in each county was greater than the PCV, which belonged to the "up to down" mode, indicating that the current eco-compensation of the river basin focuses on compensation for pollution damage, and water pollution control needs to be strengthened in the future. This research results have broadened the thinking for the quantification of basin eco-compensation and watershed water environment management.